Disruption of cholesterol homeostasis by antidepressants induces immunogenic cell death - Karla Alvarez-Valadez; Jonathan G. Pol; Guido Kroemer; Mojgan Djavaheri-Mergny (OncoImmunology)
Sertraline and indatraline are two antidepressants that function as serotonin reuptake inhibitors and have demonstrated promising anticancer potential, although their precise mechanisms of action remain unclear. Both compounds trigger cholesterol accumulation within lysosomes followed by lysosomal membrane permeabilization, ultimately leading to the activation of immunogenic cell death (ICD). This, in turn, triggers a T cell-mediated adaptive immune response that facilitates significant tumor control.